Fault Lines: Views across Haiti’s Divide - BEVERLY BELL (Cornell University Press, 2013)
Fault Lines focuses on the fi rst year after the quake, peering deep into the cracks opened in the society, economy, and polity. It casts a backward look at history to examine how such deep social fault lines developed in the fi rst place. The book looks at what movements are doing to pry apart those cracks and wrest structural change from deep within. It studies ground level, where individuals are trying to straddle the divide every day, keeping their families alive and safe on shifting terrain. And it throws a forward glance at Haitians’ visions for the future, in which they hope to fi nd themselves on even, solid ground. The book tells of the alternative principles and practices that the grassroots have tried to establish over time. You will read about the commitment to community and sharing, what Haitians call solidarity, which is not alternative at all but an ancient norm. Fault Lines describes how the old practices went into overdrive after the event, literally from the moment of the earth’s heaving. They began with the search-andrescue operations, which, contrary to international media images, were not led by foreign soldiers with German shepherds but by common citizens. First responders tell the stories of those they saved and those they couldn’t as they toiled around the clock for days, sometimes with nothing more than their fi ngers, to free people from inside buildings and under rubble. The book describes the citizen relief efforts that fi lled the gaping chasm between foreign donations and the urgent needs of survivors. You will read how these second responders who addressed recovery needs after the earliest moments of crisis—people who were more than likely homeless or hungry themselves—drew on the culture of solidarity to spontaneously offer lodging, medical care, food, and other sustenance. You will also learn about the organized aid programs that community groups launched, based in dignity, respect, and self-suffi ciency. Some explicitly tried to model the world they wanted to see.